Autour d’un Outrenoir de Pierre Soulages - Pauline Hélou-de la Grandière; Amandine Meunier (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Collaborations in conservation are frequent but are mostly organized empirically: a methodology is proposed here, using medecine and management’s tools. This paper provides an opportunity to revisit this particular exemplary experience in terms of the necessary coordination and interdisciplinary collaboration.